Perancangan Interior Bowling dan Billiard Club di Surabaya - Jacky Santosa; mariana wibowo (Intra, 2014)
Bowling and Billiard Club is a form of recreation that could accommodate the community's needs, especially Surabaya. As the information spread and people's interest to try something new rise, availability of functional Bowling and Billiard facility is needed. Hence, appears the idea to provide a recreational and sport facility which applies